2023
DOI: 10.3390/w15234138
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Estimation of the Composite Hazard of Landslides and Flash Floods Utilizing an Artificial Intelligence Approach

Mohamed Wahba,
Mustafa El-Rawy,
Nassir Al-Arifi
et al.

Abstract: Landslides and flash floods are significant natural hazards with substantial risks to human settlements and the environment, and understanding their interconnection is vital. This research investigates the hazards of landslides and floods in two adopted basins in the Yamaguchi and Shimane prefectures, Japan. This study utilized ten environmental variables alongside categories representing landslide-prone, non-landslide, flooded, and non-flooded areas. Employing a machine-learning approach, namely, a LASSO regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The runoff propagation and runoff velocity were spatially mapped for a time step of 6 hr, as shown in Figure 11a-f. After about 18 hr from the outset of the storm, the flow inundated most of the study area. It is logically observed that when comparing the region's elevation map with the estimated floodplain map, the concentration of the flow is anticipated to accrue in the lower-lying region where the likelihood of flood hazard is projected to be considerably elevated, as deduced by previous studies [29,45]. The region has an area of about 35 hectares containing 938 buildings.…”
Section: Pre-mitigation Resultsmentioning
confidence: 81%
“…The runoff propagation and runoff velocity were spatially mapped for a time step of 6 hr, as shown in Figure 11a-f. After about 18 hr from the outset of the storm, the flow inundated most of the study area. It is logically observed that when comparing the region's elevation map with the estimated floodplain map, the concentration of the flow is anticipated to accrue in the lower-lying region where the likelihood of flood hazard is projected to be considerably elevated, as deduced by previous studies [29,45]. The region has an area of about 35 hectares containing 938 buildings.…”
Section: Pre-mitigation Resultsmentioning
confidence: 81%
“…Many of these studies leverage GIS technology or other mapping platforms. Various previous research efforts have concentrated on the use of GIS and remote sensing technologies combined with other innovative technologies for assessing and predicting landslide disasters [68][69][70][71][72][73] and designing early warning systems for landslide disasters [74][75][76].…”
Section: Related Workmentioning
confidence: 99%
“…Artificial intelligence has also been widely used in sensing and assessment processes, as demonstrated in studies by Karantanellis et al [77], Selamat et al [78], and Sun et al [79], and Wahba et al [72]. Additional research by Pennington et al [80] and Ofli et al [81] has developed tools for reporting landslide incidents globally and in near real-time using social media and artificial intelligence.…”
Section: Related Workmentioning
confidence: 99%